Antioxidant Effects of Salidroside in the Cardiovascular System - Siyu Sun; Qinhui Tuo; Dongxu Li; Xiulong Wang; Xuefang Li; Yiyue Zhang; Guoan Zhao; Fei Lin (2020)
Cardiovascular disease is one of the main human health risks, and the incidence is increasing. Salidroside is an important bioactive component of Rhodiola rosea L., which is used to treat Alzheimer’s disease, tumor, depression, and other diseases. Recent studies have shown that salidroside has therapeutic effects, to some degree, in cardiovascular diseases via an antioxidative mechanism. However, evidence‐based clinical data supporting the effectiveness of salidroside in the treatment of cardiovascular diseases are limited. In this review, we discuss the effects of salidroside on cardiovascular risk factors and cardiovascular diseases and highlight potential antioxidant therapeutic strategies.